Gereja Mengambil Keputusan Etis di Era Digital dengan Budaya Algoritmik - Maxi Marthinus Mantow; Denny Tarumingi; Ineke Tombeng (Sekolah Tinggi Teologi Sriwijaya, 2026)
The emergence of digital and algorithmic culture has significantly transformed ethical decision-making within the church in contemporary society. This article examines ecclesial ethical discernment through Paul Tillich’s method of correlation in the context of the Gereja Masehi Injili di Minahasa (GMIM). Using a constructive theological approach, the study argues that algorithmic culture is not merely a technological framework but an existential condition shaping ecclesial authority, moral perception, and theological reflection. The church exists within tensions between empirical digital realities (das Sein) and normative Christian ideals (das Sollen). Algorithmic logic characterized by virality, visibility, and engagement increasingly influences ethical judgments and creates new forms of moral ambiguity within church life. This article proposes the Digital Ecclesial Ethical Discernment (DEED) model as a framework integrating existential digital challenges with Christian ethical norms such as agape, veritas, dikaiosyne, responsibility, and imago Dei. The model offers a structured and contextual approach for ecclesial ethical decision-making within contemporary digital transformation.